Bowel cancer screening. Issue 3 (March 2017) - Carney, Kate E.; Coyne, Peter E.
Abstract: Colorectal cancer (CRC) is the third most common cancer in both males and females in the UK giving rise to approximately 40, 000 new cancer cases per year. It arises from polyps as part of the adenoma-carcinoma sequence. Early detection can aid treatment and improve outcomes. Faecal occult blood (FOBt) and direct imaging using colonoscopy/sigmoidoscopy has been shown to be advantageous in the detection of polyps and earlier cancer. We review the evidence and provide summaries of current strategies as well as future potential developments.